2017
DOI: 10.1016/j.amepre.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The Social Determinants of Chronic Disease

Abstract: This review article addresses the concept of the social determinants of health (SDH), selected theories, and its application in studies of chronic disease. Once ignored or regarded only as distant or secondary influences on health and disease, social determinants have been increasingly acknowledged as fundamental causes of health afflictions. For the purposes of this discussion, SDH refers to SDH variables directly relevant to chronic diseases and, in some circumstances, obesity, in the research agenda of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
276
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(313 citation statements)
references
References 66 publications
(74 reference statements)
10
276
0
9
Order By: Relevance
“…The homeless cannot shelter in place 59 , families in housing without running water cannot wash their hands frequently 60 , people who are detained by a state (for example, in jails, prisons, immigrant detention centres or refugee camps) may lack space to implement physical distancing, people without health insurance may delay or avoid seeking testing or treatment, people who rely on public transportation cannot always avoid large crowds and low-wage workers are often in occupations (for example, service, retail, cleaning, agricultural labour) where remote work is impossible and employers do not offer paid sick leave 61 . Economic disadvantage is also associated with the pre-existing conditions associated with higher morbidity rates once infected, such as compromised immune systems, diabetes, heart disease and chronic lung diseases like asthma and chronic obstructive pulmonary disease 62 . We expect that, as in natural hazards, the economically disadvantaged will be most likely to be exposed to the hazard, most susceptible to harm from it and most likely to experience negative outcomes from it 63,64 .…”
Section: Social Inequalitymentioning
confidence: 99%
“…The homeless cannot shelter in place 59 , families in housing without running water cannot wash their hands frequently 60 , people who are detained by a state (for example, in jails, prisons, immigrant detention centres or refugee camps) may lack space to implement physical distancing, people without health insurance may delay or avoid seeking testing or treatment, people who rely on public transportation cannot always avoid large crowds and low-wage workers are often in occupations (for example, service, retail, cleaning, agricultural labour) where remote work is impossible and employers do not offer paid sick leave 61 . Economic disadvantage is also associated with the pre-existing conditions associated with higher morbidity rates once infected, such as compromised immune systems, diabetes, heart disease and chronic lung diseases like asthma and chronic obstructive pulmonary disease 62 . We expect that, as in natural hazards, the economically disadvantaged will be most likely to be exposed to the hazard, most susceptible to harm from it and most likely to experience negative outcomes from it 63,64 .…”
Section: Social Inequalitymentioning
confidence: 99%
“…21 Using tobacco and alcohol, eating an unhealthy diet, and being physically inactive are socially patterned HRBs that drive the chronic disease burden observed in the United States. [21][22][23][24][25][26] Often initiated during childhood, adolescence, and early adulthood, these highly prevalent HRBs are known to cluster within individuals and populations. [27][28][29] For example, a populationbased study indicated that more than half of U.S. adults report engaging in two or more HRBs, including smoking cigarettes, engaging in risky drinking, being physical inactive, and being overweight.…”
Section: The Burden Of Chronic Diseasementioning
confidence: 99%
“…Age has been shown to be a key determinant of obesity, with middle-aged adults having a far greater likelihood of being obese compared to older-aged and younger-aged adult groups (Ogden et al 2010;NCHS 2017;Hales et al, 2018). Race and ethnicity are frequently regarded as reliable predictors of obesity where minority populations are considered to be especially vulnerable to higher rates of obesity (Cockerham et al, 2017;Giuntella & Stella, 2017;Segal et al, 2017;Sohn et al, 2017). The percentage of households receiving SNAP benefits (formerly known as food stamps) was included because there is vigorous debate as to whether the program increases or decreases obesity rates in low-income communities (Meyerhoefer & Pylypchuk, 2008;DeBono, Ross, & Berrang-Ford, 2012;Gundersen, 2016;Segal et al, 2017;Burke et al, 2019).…”
Section: Datamentioning
confidence: 99%
“…Factors beyond genetics play a central role in the likelihood of an individual becoming obese. Such factors include those primarily related to lifestyle (e.g., diet and physical activity) and social networks (e.g., media and peer pressure) (Christakis & Fowler, 2007;Carrell, Hoekstra, & West, 2011;Hawkes, et al 2015;Cockerham, Hamby, & Oates, 2017), as well as other geographic considerations (e.g., urban areas vs. rural areas and accessibility) and the role of the built environment (Cummins et al, 2007, Larson & Story, 2009Swinburn et al, 2011;Thorpe et al, 2015;Jahagirdar & Ernest, 2017). An enormous body of literature exists that examines the factors associated with obesity and potential approaches to mitigate the issue (e.g., Kleinert & Horton, 2015;Roberto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%